Microcontroller based dual energy Moringa leaf dryer design and development - Saifuddin Muhammad Jalil; Husaini Husaini; Rizal Munadi; Ira Devi Sara (International Journal of Power Electronics and Drive Systems (IJPEDS), 2022)
This paper presents the design and development of an automatic dual energy solar powered Moringa dryer used to remove moisture. Moringa leaves are circulated by hot air evenly in a cylindrical mesh of aluminum mesh which rotates at 20 revolutions per minute through which hot air is passed to extract moisture from the leaves. The Arduino Uno or Atmega32 microcontroller works in conjunction with appropriate sensors to monitor and control humidity, moisture content, motor speed, room temperature, heater, and fan. Based on the moisture content in the Moringa leaves, the sensor sends a control signal to the controller. The results showed a good response in removing the initial moisture content from 18.5% to the final moisture content to 4% of green leaves without changing the nutritional value. Qualitative analysis showed that traditional drying, namely open drying, drying Moringa leaves each for 3 days in 12 hours with a final moisture content of 7%, while double solar drying only takes 3 days in 12 hours with a final moisture content of 4%, and produce better quality Moringa leaves. High efficiency in the drying process of Moringa leaves compared to traditional drying, where this tool can dry Moringa leaves faster by 3%.